A chirp scaling algorithm based on the method of series reversion for bistatic SAR. Issue 25 (27th June 2022) - Wu, Haoran; Cha, Hao; Ning, Mingqiang; Zhang, Peng
Abstract: For the problem that the existing chirp scaling algorithm based on the method of series reversion (MSRCSA) needs to approximate the range cell migration (RCM) into a linear term of range and causes a larger range cell migration correction (RCMC) error, we propose an improved MSRCSA, which is able to focus azimuth‐variation bistatic SAR. Firstly, to avoid the linear approximation for RCM, this paper derives a new curvature factor varying with the azimuth frequency and range, utilizing to describe RCM without any approximation. Secondly, since the new curvature factor is different with the traditional curvature factor varying only with the azimuth frequency, a new scaling function is given to modulate the echo signal so that the required range‐variant RCMC shift can be implemented by using phase multiplies. Thirdly, the proposed MSRCSA is implemented by utilizing three phase multiplications and four fast Fourier transforms (FFTs). Finally, the good performance of the proposed MSRCSA is examined by comparing the imaging result of the proposed MSRCSA with that of the existing MSRCSA.